Suggested program for the correction of articulatory defects among educable mentally retarded children - De la Cruz, Leonila A. 1945- (Quezon City College of Education, University of the Philippines Diliman, 1970)
The purpose of the study was to gather procedures, techniques, materials, devices and activities that are necessary to make a meaningful and effective speech correction program for the educable mentally retarded children in the elementary level. The study was put into shape through intensive library research work. It showed that concrete materials and colorful attractive pictures and devices are indispensable in speech correction, specially with the EMR. The devices and materials and their uses must be made familiar to the children before using them so that they find joy in their experience in manipulating them. Speech must be taught in true-to-life situations so that experiences are meaningful. Many games, riddles, poems, rhymes and jingles and songs can be adapted by the teacher in her class from the period of stimulation to their final step of speech correction. She may also modify or create materials, when necessary, to meet the needs of her pupils and the group.
Vita.
Thesis (Master of Arts in Teaching - Special Education)--University of the Philippines, Diliman.
Keywords: Articulation disorders; Speech disorders; Children with mental disabilities -- Education -- Philippines; Mental retardation -- Philippines